Analisis Asuransi Jiwa dengan manajemen risiko menggunakan ISO 31000 - Cornelius, Novrico (TeIKa, 2025)
This research aims to analyse the risk of life insurance claim at PT Allianz Insurance Balikpapan Branch with descriptive qualitative approach. The data is analysed using the ISO 31000 method. The result of the study shows that ISO 31000 method helps to identify claim risk as a protection for the company. The risk assessment process is conducted in three stages: (1) identification since the submission of Insurance Application Letter and Participant's Statement, (2) analysis of frequency relationship and risk severity, and (3) physical and financial risk evaluation. In conclusion, the risk assessment of life insurance claims with the highest risk is fraudulent claims with the highest score. The implication of these findings is to increase the reliability of risk management processes that can strengthen company security, reduce potential financial losses, and increase customer confidence in insurance companies.